What if We Contain Multiple Morally Relevant Subjects?. Issue 3 (September 2022) - Crummett, Dustin
Abstract: First, I introduce the concept of a "non-agential subject, " where a non-agential subject (1) exists within an organism and (2) has phenomenally conscious experiences in a morally significant way, but (3) is not morally responsible for (some or all of) the organism's voluntary actions. Second, I argue that it's a live possibility that typical adult humans contain non-agential subjects. Finally, I argue that, if there are non-agential subjects, this has important and surprising implications for a variety of ethical issues. Accordingly, ethicists should pay more attention to whether there are non-agential subjects and what their implications for ethics would be.